Development and validation of ultraviolet spectrophotometric method for the simultaneous estimation of sitagliptin phosphate and dapagliflozin in bulk and marketed formulation - Khatik, Mohini A. (Asian Journal of Pharmaceutics (AJP), 2025)
The necessity for trustworthy analytical techniques for combination therapy quality control has increased because of the increase in the incidence of type 2 diabetes mellitus. Sitagliptin phosphate and dapagliflozin, used in combination for glycemic control, require a validated method for their simultaneous quantification in pharmaceutical formulations. This work attempts to establish a simple, precise, and accurate ultraviolet (UV) spectrophotometric approach. Materials and Methods: UV spectrophotometric testing was done at 266 nm for Sita and 229 nm for Dapa. The technique was validated following the International Conference on Harmonisation Q2 (R1) guideline, and various parameters were checked, including linearity, precision, accuracy, limit of detection, limit of quantitation, ruggedness, and robustness. Results: Excellent linearity was demonstrated by the UV spectrophotometric technique with coefficients of correlation (R2) for >0.999 for both drugs. Conclusion: The newly developed UV method is simple, sensitive, and reliable for simultaneously estimating sitagliptin phosphate and dapagliflozin in bulk and commercial formulations.